Wireless multi-lateral optofluidic microsystems for real-time programmable optogenetics and photopharmacology - Wu, Yixin; Wu, Mingzheng; Vazquez-Guardado, Abraham; Kim, Joohee; Zhang, Xin; Avila, Raudel; Kim, Jin-Tae; Deng, Yujun; Yu, Yongjoon; Melzer, Sarah; Bai, Yun; Yoon, Hyoseo; et al. (Nature Publishing Group, 2022)
Wireless delivery of both light and pharmacological agents is important for optogenetic and other mechanistic experiments in the brain. Here the authors present a wireless real-time programmable optofluidic platform that enables optogenetics and photopharmacology experiments that require real-time precise control of light and drug delivery. In vivo optogenetics and photopharmacology are two techniques for controlling neuronal activity that have immense potential in neuroscience research. Their applications in tether-free groups of animals have been limited in part due to tools availability. Here, we present a wireless, battery-free, programable multilateral optofluidic platform with user-selected modalities for optogenetics, pharmacology and photopharmacology. This system features mechanically compliant microfluidic and electronic interconnects, capabilities for dynamic control over the rates of drug delivery and real-time programmability, simultaneously for up to 256 separate devices in a single cage environment. Our behavioral experiments demonstrate control of motor behaviors in grouped mice through in vivo optogenetics with co-located gene delivery and controlled photolysis of caged glutamate. These optofluidic systems may expand the scope of wireless techniques to study neural processing in animal models.